Tongue sole creatine kinases function as DAMP and activate antimicrobial immunity via TLR2 - Li, Xin; Jiang, Shuai; Sun, Li (Frontiers in Immunology, 2023)
Creatine kinase (CK) is an enzyme that regulates adenosine triphosphate (ATP) metabolism to maintain energy homeostasis. Although CK has been reported to be involved in pathogen infection, the immune function of CK remains elusive. In this study, we identified two muscle-type CK from the teleost tongue sole Cynoglossus semilaevis (designated CsCKM-1 and CsCKM-2). Bacterial infection modulated CsCKM-1/2 expression in tongue sole tissues and induced the release of CsCKM-1/2 into serum. Recombinant CsCKM-1/2 (rCsCKM-1/2) exhibited robust kinase activity and bound to bacterial pathogens and pathogen-associated molecular patterns. rCsCKM-1/2 also bound to tongue sole peripheral blood leukocytes (PBLs) and promoted PBLs to uptake bacterial pathogens, inhibit bacterial proliferation, and express proinflammatory cytokines. When co-expressed in HEK293T cells, CsCKM-1/2 were found to interact with the leucine rich domain of toll-like receptor 2 (TLR2). The presence of TLR2 antagonist significantly reduced CsCKM-1/2-induced immune response and antibacterial effect. Taken together, these results indicated that tongue sole creatine kinases function as damage-associated molecular pattern (DAMP) molecules and play an important role in antimicrobial immunity via TLR2.